3D Bio-convective nanofluid Bödewadt slip flow comprising gyrotactic microorganisms over a stretched stationary disk with modified Fourier law - Zhou, Shuang-Shuang; Ramzan, Muhammad; Howari, Fares; Kadry, Seifedine; Chu, Yu-Ming; Malik, M Y (Physica scripta, 2021)
The renowned Bödewadt flow problem is considered here for the case of Bio-convective nanofluid flow encompassing gyrotactic microorganisms over a stationary disk. The flow is initiated owing to the rotation of water-based nanofluid which is at a large distance from an immovable disk. The analysis is performed with modified Fourier law in a Darcy-Forchheimer spongy media accompanied by slip and zero mass flux conditions at the surface. The subject Bödewadt nanofluid flow is considered with gyrotactic microorganisms and Cattaneo-Christov (C-C) heat flux effects for the first time. Conformist Von Kármán relations are affianced to attain a similar governing system of differential equations. An efficient MATLAB software-based numerical scheme bvp4c is employed to address the envisaged novel mathematical model. An outstanding synchronization is achieved when a comparative statement is formulated in a limiting case. Outcomes of the proclaimed parameters versus involved distributions are discussed with logical reasoning. It is comprehended that the microorganism density boundary layer is prominent for higher values of the Peclet number. Furthermore, it is remarked that the fluid temperature is diminished for significant values of the thermal relaxation time.